Enhancement of the tribological properties of carbon fiber/epoxy composite by grafting carbon nanotubes onto fibers. Issue 55 (18th May 2016) - Chen, Beibei; Li, Xiaofang; Yang, Jin; Huang, Hong; Peng, Weixiang; Li, Changsheng; Zhang, Zhaozhu
Abstract : Morphology of CF before and after grafting CNT; wear resistance of CF/EP composite. Abstract : A novel method is developed for improving the tribological properties of a carbon fiber reinforced epoxy resin composite (CF/EP) by grafting carbon nanotubes (CNT) onto the CF surface using polyamide-amine (PAMAM) as the bridging agent. The friction and wear properties of the corresponding composites are comparatively investigated using a UMT-2 friction and wear tester. Results show that the PAMAM macromolecule with multiple amino groups is firstly absorbed onto the surface of functionalized CF by chemical and physical adsorption, and then, functionalized CNT is successfully grafted onto the CF surface by reacting with PAMAM. More importantly, the tribological properties of the CF/EP composite have been improved obviously after grafting CNT onto the CF surface. This is because CNT enhances the mechanical interlocking and chemical bonding interactions between CF and EP, preventing CF from being pulled out under shear stress during the friction and wear process. In addition, CNT with excellent mechanical strength can effectively share the applied load to protect CF from being broken as a result of stress concentration.